2021
DOI: 10.1007/s13744-021-00896-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacillus thuringiensis Strains for the Management of Lepidopteran Pests

Abstract: Bacillus thuringiensis (Bt)-based bioinsecticides and transgenic plants expressing proteins with insecticidal activity (Cry and Vip) have been successfully used in several integrated pest management programs worldwide. Lepidoptera comprise some of the most economically important insect pests of the major agricultural crops. In this study, the toxicity of 150 Bt strains was evaluated against Helicoverpa armigera (Hübner) larvae. Eight strains (426, 520B, 1636, 1641, 1644, 1648, 1657 and 1658) showed high insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The strain showed insecticidal activity against H. armigera (LC50 of 0.294 µg.cm-2) and to C. includens from both origins, with LC 50 0.277 µg.cm -2 , and 0.398 µg.cm -2 , respectively ( Table 1 ). This LC 50 of in both species is comparable to previous bioactive B. thuringiensis isolates with potential use in microbial control ( Ignoffo et al, 1977 ; Pinheiro and Valicente, 2021 ).…”
supporting
confidence: 73%
“…The strain showed insecticidal activity against H. armigera (LC50 of 0.294 µg.cm-2) and to C. includens from both origins, with LC 50 0.277 µg.cm -2 , and 0.398 µg.cm -2 , respectively ( Table 1 ). This LC 50 of in both species is comparable to previous bioactive B. thuringiensis isolates with potential use in microbial control ( Ignoffo et al, 1977 ; Pinheiro and Valicente, 2021 ).…”
supporting
confidence: 73%
“…(2009) used selective bioassays to show that seven of 100 Bt strains, in addition to HD‐1, showed high toxicity to S. eridania larvae. Pinheiro and Valicente (2021) demonstrated that eight of 150 Bt strains caused mortality rates higher than 75% to H. armigera . These results corroborate our findings that Bt could be a viable alternative for insect pest control.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported high mortality levels after Bt ingestion by S. frugiperda larvae(Monnerat et al, 2007;Valicente et al, 2010). dosSantos et al (2009) used selective bioassays to show that seven of 100 Bt strains, in addition to HD-1, showed high toxicity to S. eridania larvae Pinheiro and Valicente (2021). demonstrated that eight of 150 Bt strains caused mortality rates higher than 75% to H. armigera.…”
mentioning
confidence: 99%
“…The second approach is crop breeding to develop insect−resistant cultivars, mainly via genetic engineering. Bacillus thuringiensis (Bt) crystal protein genes have been widely used in crops to resist chewing pests [1,2]. Nevertheless, transgenic Bt crops can resist only limited types of pests.…”
Section: Introductionmentioning
confidence: 99%